Analysis of the Influence of Labor, Unemployment Rate, and Education on Poverty Levels in Ngawi Regency - Asmynenndar, Rafi Fahrezi; Primandhana, Wiwin Priana (PT. Riset Press International, 2025)
Poverty structural which is the most dominant in the Regency Ngawi. The poverty that occurs consequence imbalance in system economic, social, and policy, which causes part public difficult go out from poverty, although they own will For working. Development sector education in the Regency Ngawi Still limited and quality low impact on low welfare population, reflected from height number unemployment among poor people. Agriculture traditional Still dominant However not enough capable absorb power Work in a way effective. Meanwhilethat, modern industry and services have not developed, so that opportunities for productive work are still limited. Research This do testing hypothesis with use analysis regression multiple. Labor Force Variables and Unemployment Rate show positive influence However No significant to level poverty in the Ngawi Regency. The Education variable shows connection negative and influential significant to level poverty in the Regency Ngawi.